Overcoming institutional voids via arbitration - Pinkham, Brian C; Peng, Mike W (Journal of International Business Studies, 2017)
Extending the literature on institutional voids, we introduce theory from law that highlights the ability of firms to choose the laws and enforcement mechanisms that govern their international joint ventures (IJVs). Specifically, firms may overcome institutional voids by borrowing institutions via binding international commercial arbitration (BICA) rather than relying on host-market institutions. Leveraging an institution-based view, we develop a theoretical framework to articulate the conditions under which IJV partners may choose BICA as opposed to domestic courts to overcome institutional voids in host markets.